HUBUNGAN TINGKAT PENGETAHUAN DENGAN KONSEP DIRI REMAJA PUTRI YANG MENGALAMI JERAWAT (AKNE VULGARIS) - ridwan, achmad; astutik, wahyu sri; astutik, Yuyun dwi (Akademi Keperawatan Pamenang, 2010)
Teen-Age is a period of the happening of physical change and also mental. One of change of physical that happened is hormone, which can trigger incidence of pimple and also influent adolescent appearance. This purpose of this research was to know influent mount knowledge to adolescent self concept experiencing of pimply in SMA Muhammadiyah I Pare. This Research design used Cross Sectional with population of student of SMA Muhammadiyah I Pare, with 30 responder used total sampling technique. The analyzed of correlation of Chi Square got P(0.557 > α( 0.05), it means H0 accepted and H1 rejected, it meant there was no influent of mount knowledge to concept of adolescent experiencing of pimply in SMA Muhammadiyah I Pare.The knowledge enough is important to adolescent, especially knowledge about pimply. For that, parent or family and environment of school like teacher as a closest adolescently so that give positive and responds support in each change experienced of adolescent. Because responds from people closest can influence adolescent assessment to their self, and indirectly have an effect on to growth self conception.